(untitled) (Current Horticulture, 2024)
An experiment was conducted during rabi, 2021-22 at College of Agriculture, Jodhpur to assess the effect of plant growth regulators (PGRs) on the growth, flowering, and fruiting characteristics; and quality of tomato (Solanum lycopersicum L.) in a randomized block design with three replications comprising 10 treatments. Three levels each of GA3, 4-CPA, and NAA along with control were used. There was maximum plant height (47.2 cm, 61.3 cm, and 80.9 cm at 45 DAT, 60 DAT, and final harvesting, respectively), number of branches (19.4/plant), leaf area (30.6 cm2), TSS (5.41˚Brix) and ascorbic acid (22.8 mg/100g) over the control with GA3@75 ppm, whereas minimum acidity (0.46 %) was recorded with NAA@75 ppm. The significantly higher fruit length (6.7 cm), fruit diameter (7.2cm), and fruit firmness (2.6 kg/cm2) were recorded with 4-CPA@75 ppm. The maximum number of fruit clusters (12.0/plant), number of flowers (5.4/cluster), number of fruits (3.2/cluster), number of fruits (38.1/plant), fruit setting (59.7%), fruit weight (84.3 g) and lycopene content (6.5 mg/100g) were observed with NAA@75 ppm.